A History of Silences. Issue 3 (September 2017) - Vincent, Alexandre
Abstract : This paper, grounded in a critical reading of Alain Corbin's recent History of Silence, proposes a twofold development. The first part is methodological, arguing for the necessity of studying the acoustic phenomena of the past in a way that is distinct from emotion and does not focus solely on conveying experience. The historiography of the notion of "soundscapes, " invented by musicologist Raymond Murray Schafer, is used to assess the contribution of "sound studies, " "sensory history, " and the anthropology of the senses. The heuristic capacities of this notion are emphasized, as is the need to locate it within a coherent topographical and chronological framework. The second section of the article develops a case study based on these methodological prescriptions, focusing on silence in the religious rites of ancient Rome. The acoustic frame of ritual perfection, silentium was also a category of Roman religious law and very far from the quest for interiority and spiritual life that Corbin considers a natural part of silence. An analysis of the nature and function of silence in two different rites, taking the auspices and sacrifice, confirms the need for a thorough and contextualized historical approach to acoustic phenomena: behind a unified terminology lie two radically different acoustic realities.